If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -3k + 6k = 2k + -3 Combine like terms: -3k + 6k = 3k 8 + 3k = 2k + -3 Reorder the terms: 8 + 3k = -3 + 2k Solving 8 + 3k = -3 + 2k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-2k' to each side of the equation. 8 + 3k + -2k = -3 + 2k + -2k Combine like terms: 3k + -2k = 1k 8 + 1k = -3 + 2k + -2k Combine like terms: 2k + -2k = 0 8 + 1k = -3 + 0 8 + 1k = -3 Add '-8' to each side of the equation. 8 + -8 + 1k = -3 + -8 Combine like terms: 8 + -8 = 0 0 + 1k = -3 + -8 1k = -3 + -8 Combine like terms: -3 + -8 = -11 1k = -11 Divide each side by '1'. k = -11 Simplifying k = -11
| -4(x+3)-7=-3x-15 | | 6(w-3)-(2w-5)=3w | | y=-8/9x-8/9 | | -5+7x+7=8(x+3)-9 | | 12R=1/4M-5 | | 4x-28y=44 | | -2y+13=14-y | | g(p+2)=3x^2+3x+1 | | -2-k=-8 | | -4c+18=5c | | (1/3)9squarred | | 7x+8-5x=-2 | | 7b+3=5b-11 | | -6+6x+7=(x+1)-2 | | -40-8=6s | | -2=0-1/5j | | 9-5a+a=-3 | | 6n-7(n-1)=12 | | 2m+6=2m-2 | | 5(z+6)=2+3z | | (6/5(p-4))-(6/5p) | | 0=16t^2+138t+55 | | 6a+2a+12=7+6a+3 | | 4x-5+2x=13 | | y=4x^2-6x-7 | | 0=16t^2+138t+c | | x^2-y^2=50 | | x+8+5x=2-2x | | 2x^3+7x^2-15=0 | | 7.6x-1.6=13.6 | | 2k=56 | | m-7m+6=20 |